Speaking order predicts memory conformity after accounting for exposure to misinformation - Hewitt, Lauren; Kane, Robert; Garry, M. (Springer New York LLC, 2013)
When people discuss their experiences, they can later report seeing things that they never saw, simply because they heard about those things in the discussion. One factor that may contribute to this effect is the order in which people speak; some research has investigated this issue, but it remains unclear whether a relationship exists between memory conformity and speaking order. We explored this question using data from five previous memory conformity experiments. The results provide evidence of an association between speaking order and memory conformity, such that people who spoke first in a discussion were misled less often than people who did not. These results build on previous research by demonstrating that the association could not have been caused by differences in opportunities to be misled. We could not draw conclusions about causality from the exploratory analyses, but ruled out several simple explanations of the results, and considered a variety of social and cognitive mechanisms that might account for the association. Further investigation will be required to tease apart the possible mechanisms that underlie the relationship between speaking order and memory conformity.